Valuasi Ekonomi Sumberdaya Pesisir dan Laut dalam Kebijakan Penataan Ruang Wilayah Pesisir dan Laut - Sabet, Fia Birtha Al Sabet; Pungki Ari, Wibowo (OECONOMICUS Journal of Economics, 2022)
The application of economic instruments in the spatial planning of coastal and marine areas is very important considering that Indonesia is a mega biodiversity country with abundant biodiversity. Spatial planning for coastal and marine areas based on the assessment of ecosystem services has both opportunities and constraints. The main opportunity in using ecosystem services assessment is that the spatial arrangement can be reconstructed according to the framework of ecosystem services and incorporate the relevant ecosystem services approach of the plan